(1385) labor migration and its impact on Egyptian labor market هجرة العمالة وتأثيرها على سوق العمل المصري - arman, ismail M. I. (The Institute Of National Planning., 2018)
Traditional migration theory postulate that an individual's decision to migrate from his original residential location to new and possibily distant place is based on a comparison of economic attributes characterizing the two localities.